Organic-inorganic composite composition

JP7633016B2Active Publication Date: 2025-02-19TEIJIN LTD

Patent Information

Application Number
JP2020184219
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-04
Publication Date
2025-02-19
Estimated Expiration
2040-11-04

AI Technical Summary

Benefits of technology

【0022】 本発明によれば、重合鎖末端に特定の構造単位を有するポリカーボネート樹脂と、無機微粒子とを用いることで、無機微粒子のポリカーボネート樹脂への分散性を向上させた、透明性、成形性、屈折率に優れる有機無機複合組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633016000015
    Figure 0007633016000015
  • Figure 0007633016000016
    Figure 0007633016000016
  • Figure 0007633016000001
    Figure 0007633016000001
Patent Text Reader

Abstract

To provide an organic-inorganic composite composition that includes inorganic fine particles uniformly dispersed in polycarbonate resin, wherein the composition can be practically used as an optical resin even after molded.SOLUTION: An organic-inorganic composite composition includes a polycarbonate resin having a structural unit of the formula (1) at a polymer chain end, and inorganic fine particles. (In the formula (1), R1 and R2 may be the same or different and each denote at least one selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, a cycloalkyl group, a cycloalkoxy group, an alkenyl group, an aryl group, an aryloxy group, an aralkyl group, an aralkyloxy group, a nitro group, an aldehyde group and a cyano group, a and b each represent an integer of 1-2, X denotes a single bond or a specific S-containing group).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an organic-inorganic hybrid composition containing a polycarbonate resin and inorganic fine particles. [Background technology]

[0002] In recent years, optical materials have been actively developed. For example, in the field of optical lens materials, optical materials with high refractive index, high Abbe number, heat resistance, and excellent transparency are required. Glass, which has been used conventionally, can realize various required optical properties and has excellent environmental resistance, but has a problem of poor processability. In response to this, resin materials, which are cheaper and have excellent processability compared to glass materials, have been used for optical components. However, since resins generally have a lower refractive index than glass, it is required to increase the refractive index of the material itself in order to make optical components thinner.

[0003] One method for increasing the refractive index is to uniformly disperse fine particles of inorganic oxides such as titanium oxide and zirconium oxide in a resin. However, since such fine particles have a large surface energy, it is difficult to uniformly disperse them in a matrix resin, and thus various studies have been conducted.

[0004] As a method for uniformly dispersing fine particles in a resin, there is a method of chemically modifying the surface of fine particles with a surface modifier. For example, Patent Document 1 describes a method in which fine particles modified with a specific chemical structure are mixed with a resin to prepare a master batch, and then melt-kneaded with a thermoplastic resin to obtain a transparent resin composition. In this method, although dispersibility is improved to a certain extent by selecting a surface modifier, it is difficult to say that sufficient dispersibility is obtained. In addition, there is a problem that the content of inorganic fine particles is low and is not sufficient in terms of increasing the refractive index.

[0005] Patent Document 2 describes a method of polymerizing a polycarbonate resin and then introducing a carboxyl group into the terminal of the polycarbonate resin, and a method of copolymerizing a diol compound having a carboxyl group to obtain a carboxyl group-containing polycarbonate resin, and describes that a film composited with inorganic fine particles has excellent transparency. The method of introducing a carboxyl group into the terminal utilizes a reaction between a hydroxyl group at the polymer terminal and an acid anhydride. In this method, a multifunctional compound is used as the acid anhydride, so gelation may be a problem, especially in a processing process at high temperatures. In addition, in the copolymerization method, the carboxyl group reacts with other diol compounds during polymerization, making it difficult to control the amount of carboxyl group introduced, and the dispersion stability of inorganic fine particles may be a problem, especially under high temperature conditions. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-38012 A [Patent Document 2] JP 2018-138624 A Summary of the Invention [Problem to be solved by the invention]

[0007] In order to increase the refractive index of polycarbonate, a method of designing the molecular structure of the polymer to improve the electron density is generally used, but a method of increasing the refractive index by uniformly dispersing fine particles in the resin is hardly used in practice. This is because, in addition to the difficulty of obtaining a resin composition in which fine particles are uniformly dispersed as described above, even if such a resin composition is obtained, when the resin composition is molded, the dispersion state of the fine particles may change and the fine particles may aggregate.

[0008] Therefore, an object of the present invention is to provide an organic-inorganic hybrid composition in which inorganic fine particles are sufficiently dispersed in a polycarbonate resin, which can be practically used as an optical resin even after molding. [Means for solving the problem]

[0009] As a result of extensive research, the inventors have found that the dispersibility of inorganic fine particles in polycarbonate resin can be improved by using a polycarbonate resin having a specific structural unit at the polymer chain end, and have demonstrated that an organic-inorganic hybrid composition containing the polycarbonate resin and inorganic fine particles has excellent transparency, moldability and refractive index, thereby completing the present invention.

[0010] That is, according to the present invention, the object of the invention is achieved as follows. 1. An organic-inorganic hybrid composition comprising a polycarbonate resin having a structural unit represented by the following formula (1) at a polymer chain end, and inorganic fine particles:

[0011] [ka]

[0012] (In formula (1), R 1 and R 2 may be independent or the same, and each represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, a cycloalkyl group, a cycloalkoxy group, an alkenyl group, an aryl group, an aryloxy group, an aralkyl group, an aralkyloxy group, a nitro group, an aldehyde group, and a cyano group, a and b each represent an integer of 1 to 2, X represents a single bond or a group represented by the following formula (2):

[0013] [ka]

[0014] where R is a divalent group represented by 5represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group; R 3 and R 4 each independently represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group; R 4 The hydrogen atoms in may be substituted with carboxyl groups.

[0015] 2. The organic-inorganic hybrid composition according to item 1 above, wherein the molar ratio of the polymer chain ends is from 1.0 mol % to 10 mol % relative to 100 mol % of all carbonate repeating units. 3. The organic-inorganic hybrid composition according to item 1 or 2 above, wherein the formula (1) contains a structural unit represented by the following formula (3):

[0016] [ka]

[0017] (In formula (3), R 6 represents at least one group selected from the group consisting of a single bond, an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group.

[0018] 4. The organic-inorganic hybrid composition according to item 1 or 2 above, wherein the formula (1) contains a structural unit represented by the following formula (4):

[0019] [ka]

[0020] (In formula (4), R 7 represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group.

[0021] 5. The organic-inorganic hybrid composition according to any one of items 1 to 4 above, wherein the polycarbonate resin has a carboxyl group amount of 1 eq / ton to 200 eq / ton. 6. The organic-inorganic hybrid composition according to any one of items 1 to 5 above, wherein the surfaces of the inorganic fine particles are modified with a surface modifying agent. 7. The organic-inorganic hybrid composition according to item 6 above, wherein the surface modifier has an acidic functional group. 8. The organic-inorganic hybrid composition according to item 7 above, wherein the acidic functional group is at least one acidic functional group selected from the group consisting of a sulfonic acid group, a phosphonic acid group, a phosphinic acid group, and a carboxylic acid group. 9. The organic-inorganic hybrid composition according to any one of items 6 to 8 above, wherein the surfaces of the inorganic fine particles are modified with the surface modifying agent in an amount of 1 to 30% by mass based on the inorganic fine particles. 10. The organic-inorganic hybrid composition according to any one of items 1 to 9 above, wherein the inorganic fine particles have an average particle size of 1 to 20 nm. 11. The organic-inorganic hybrid composition according to any one of items 1 to 10 above, wherein the content of the inorganic fine particles is 1 to 50% by mass based on the polycarbonate resin. 12. The organic-inorganic hybrid composition according to any one of items 1 to 11 above, wherein the inorganic fine particles are at least one selected from the group consisting of ZrO2 (zirconium oxide), TiO2 (titanium oxide), SnO2 (tin oxide), SiO2 (silicon oxide), and Al2O3 (aluminum oxide). 13. A molded article obtained by using the organic-inorganic hybrid composition according to any one of items 1 to 12 above. 14. A film or sheet obtained by using the organic-inorganic hybrid composition according to any one of items 1 to 12 above. Effect of the Invention

[0022] According to the present invention, by using a polycarbonate resin having a specific structural unit at a polymer chain terminal and inorganic fine particles, it is possible to provide an organic-inorganic hybrid composition having excellent transparency, moldability, and refractive index, in which the dispersibility of the inorganic fine particles in the polycarbonate resin is improved. [Brief description of the drawings]

[0023] [Figure 1] The photograph in FIG. 1 shows a TEM image of the organic-inorganic composite composition prepared in Example 1. [Diagram 2] The photograph in FIG. 2 shows a TEM image of the organic-inorganic hybrid composition prepared in Comparative Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present disclosure is not limited to the following embodiments, and may be modified in various ways within the scope of the present invention.

[0025] One aspect of the present invention is characterized by using a polycarbonate resin containing a structural unit having a carboxyl group at the polymer chain end, as represented by the above formula (1). The organic-inorganic hybrid composition of the present invention has excellent dispersion stability of inorganic fine particles under high temperature conditions, and is excellent in transparency, moldability, and refractive index.

[0026] On the other hand, in the method described in the above Patent Document 2, a polymer having a carboxyl group at the side chain or end is used to provide an organic-inorganic composite composition having excellent transparency. However, according to the investigations of the present inventors, it has become clear that the transparency is reduced under high temperature conditions such as injection molding, and decomposition occurs during molding, making it impossible to obtain a molded product.

[0027] Although not intended to limit the technical scope of the present invention, the mechanism by which such effects are obtained in the present invention is presumed to be as follows. By introducing a structural unit having a carboxyl group, such as that represented by the above formula (1), into the polymer chain end of a polycarbonate resin, the surface of inorganic fine particles can be effectively coated with the structural unit, and a high level of transparency can be maintained even under high temperature conditions. Furthermore, since the surface of inorganic fine particles can be easily coated with the structural unit, active hydroxyl groups on the surface of the inorganic fine particles are effectively shielded, so that hydrolysis of the polymer under high temperature conditions can be suppressed. As a result, an organic-inorganic hybrid composition can be provided that has high transparency and is simultaneously suppressed in hydrolysis, and can be molded under high temperature conditions.

[0028] The present invention will be described in detail below.

[0029] <Polycarbonate resin> The polycarbonate resin used in the present invention is a polycarbonate resin having a structural unit represented by the following formula (1) at the polymer chain terminal.

[0030] [ka]

[0031] In formula (1), R 1 and R 2 may be independent or the same, and each represents at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, a cycloalkyl group, a cycloalkoxy group, an alkenyl group, an aryl group, an aryloxy group, an aralkyl group, an aralkyloxy group, a nitro group, an aldehyde group, and a cyano group, a and b each represent an integer of 1 to 2, X represents a single bond or a group represented by the following formula (2):

[0032] [ka]

[0033] where R is a divalent group represented by5 represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group; R 3 and R 4 each independently represents an alkylene group, an aralkylene group, or an arylene group. and a cycloalkylene group; R 4 The hydrogen atoms in may be substituted with carboxyl groups.

[0034] In the above formula (1), preferably, R 1 and R 2 R is independently at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group. 1 and R 2 When there are a plurality of each of the above, they may be the same or different.

[0035] Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.

[0036] Examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, a dodecyl group, a tetradecyl group, etc. An alkyl group having 1 to 6 carbon atoms is preferred.

[0037] Examples of the alkoxy group having 1 to 18 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentoxy group, a hexoxy group, an octoxy group, etc. An alkoxy group having 1 to 6 carbon atoms is preferred.

[0038] Examples of the cycloalkyl group having 6 to 20 carbon atoms include a cyclohexyl group, a cyclooctyl group, etc. A cycloalkyl group having 6 to 12 carbon atoms is preferred.

[0039] Preferred examples of the cycloalkoxy group having 6 to 20 carbon atoms include a cyclohexyloxy group, a cyclooctyloxy group, etc. A cycloalkoxy group having 6 to 12 carbon atoms is preferred.

[0040] Examples of the alkenyl group having 2 to 10 carbon atoms include a methenyl group, an ethenyl group, a propenyl group, a butenyl group, a pentenyl group, etc. An alkenyl group having 2 to 6 carbon atoms is preferred.

[0041] Examples of the aryl group having 6 to 14 carbon atoms include a phenyl group, a naphthyl group, etc. Examples of the aryloxy group having 6 to 14 carbon atoms include a phenyloxy group, a naphthyloxy group, etc.

[0042] Examples of the aralkyl group having 7 to 20 carbon atoms include a benzyl group, a phenylethyl group, etc. Examples of the aralkyloxy group having 7 to 20 carbon atoms include a benzyloxy group, a phenylethyloxy group, etc.

[0043] Preferably, a and b in formula (1) are each an integer of 1 to 2, and more preferably, a and b are each an integer of 1.

[0044] Preferably, R in formula (2) 5 represents at least one group selected from the group consisting of a single bond, an alkylene group having 1 to 10 carbon atoms, an aralkylene group having 7 to 20 carbon atoms, an arylene group having 6 to 10 carbon atoms, and a cycloalkylene group.

[0045] Preferably, R in formula (2) 3 and R 4 Each of them may be independent or the same, and each of them is an alkylene group, an alkylidene group, an aralkylene group, an arylene group, and a cycloalkylene group. Preferably, R 3 and R 4 may be independent or the same and are each an alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, or an aralkylene group having 7 to 20 carbon atoms, and more preferably an alkylene group having 1 to 6 carbon atoms, an arylene group having 6 to 10 carbon atoms, or an aralkylene group having 7 to 12 carbon atoms.

[0046] The molar ratio of the polymer chain end having the structural unit represented by the formula (1) is preferably 1.0 mol% or more and 10 mol% or less, more preferably 1.5 mol% or more and 8.0 mol% or less, even more preferably 2.0 mol% or more and 7.0 mol% or less, and particularly preferably 3.0 mol% or more and 6.0 mol% or less, based on 100 mol% of all carbonate repeating units in the polycarbonate resin. When it is within the above range, the effects of the present invention can be fully exhibited.

[0047] (Preferred embodiment (1)) In the present invention, a preferred embodiment (1) is one in which the above formula (1) contains a structural unit represented by the following formula (3):

[0048] [ka]

[0049] In formula (3), R 6 R represents at least one group selected from the group consisting of a single bond, an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group. 6 is preferably at least one group selected from the group consisting of a single bond, an alkylene group having 1 to 10 carbon atoms, an aralkylene group having 7 to 20 carbon atoms, an arylene group having 6 to 10 carbon atoms, and a cycloalkylene group.

[0050] The polycarbonate resin containing the structure represented by the above formula (3) at the polymer chain end is produced by using a method of using a phenolic compound having a carboxyl group as a terminal terminator in a reaction means known per se for producing a normal polycarbonate resin, or a method of performing a polymerization reaction using a phenolic compound having a carboxylic acid ester group as a terminal terminator, and then performing an acid modification reaction to modify the carboxylic acid ester group to a carboxyl group, or by using both of these methods. Examples of the polymerization reaction method include an interfacial polycondensation method, a melt transesterification method, and a solid-phase transesterification method of carbonate prepolymer. Among them, from the viewpoint of quantitatively introducing the structure represented by formula (3) at the polymer chain end, a method of using a phenolic compound having a carboxyl group or a phenolic compound having a carboxylic acid ester group, or both of them as a terminal terminator in the interfacial polycondensation method is preferred.

[0051] Examples of phenol compounds having a carboxyl group that are used as end terminators include 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, and 2-hydroxybenzoic acid. From the viewpoint of efficiency of introduction into the polymerization end, 4-hydroxybenzoic acid and 3-hydroxybenzoic acid are preferred, and 4-hydroxybenzoic acid is more preferred. These may be used alone or in combination of two or more.

[0052] Examples of phenol compounds having a carboxylate group that can be used as an end terminator include tertiary butyl 4-hydroxybenzoate, isopropyl 4-hydroxybenzoate, and methyl 4-hydroxybenzoate. Of these, tertiary butyl 4-hydroxybenzoate and isopropyl 4-hydroxybenzoate are preferred, and tertiary butyl 4-hydroxybenzoate is more preferred. These may be used alone or in combination of two or more. By making the carboxyl group into a carboxylate structure, hydrophobicity is improved and it becomes easy to quantitatively introduce the carboxyl group into the polymer chain end.

[0053] Phenol compounds not having a carboxyl group or a carboxylate group may be used in combination as a terminal terminator. Examples of phenol compounds not having a carboxyl group or a carboxylate group include phenol, m-methylphenol, p-methylphenol, m-propylphenol, p-propylphenol, 1-phenylphenol, 2-phenylphenol, p-tert-butylphenol, p-cumylphenol, isooctylphenol, and p-long chain alkylphenol. By using these phenol compounds not having a carboxyl group in combination as a terminal terminator, the amount of carboxyl groups at the polymer chain end can be quantitatively adjusted, and the thermal stability of the organic-inorganic composite composition, the dispersibility of inorganic fine particles, and the flowability during melting can be controlled.

[0054] In the method using a phenolic compound having a carboxylate group, a polycarbonate resin is produced by a polymerization reaction, and then the carboxylate group is converted to a carboxyl group by an acid modification reaction, so that the polymer chain end can have a structure represented by formula (3). The acid modification reaction can be, for example, but is not limited to, a method in which an acidic compound is applied, a method of heat treatment, or other known methods. From the viewpoint of reaction efficiency, a method using an acidic compound is preferred. The acidic compound can be, for example, but is not limited to, a strong acidic compound such as trifluoroacetic acid or hydrochloric acid. From the viewpoint of reaction efficiency, trifluoroacetic acid is particularly preferred.

[0055] The production process of the acid modification reaction using an acidic compound may be, for example, a process of dissolving a solidified polymer in a solvent and reacting with an acidic compound, or in the case of a polymerization method using a solvent such as an interfacial polycondensation method, a process of reacting an acidic compound with a polymer solution after the polymerization reaction has been completed may be used.

[0056] (Preferred embodiment (2)) In the preferred embodiment (2) of the present invention, the formula (1) preferably contains a structural unit represented by the following formula (4):

[0057] [ka]

[0058] In formula (4), R 7 R represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group. 7 is preferably an alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, or an aralkylene group having 7 to 20 carbon atoms, and more preferably an alkylene group having 1 to 6 carbon atoms, an arylene group having 6 to 10 carbon atoms, or an aralkylene group having 7 to 12 carbon atoms.

[0059] The method for producing the polycarbonate resin having the structure represented by the formula (4) used in the present invention includes, for example, a step (I) of producing a polycarbonate resin having a carbon-carbon double bond, and a step (I) of reacting the polycarbonate resin with a thiol compound having a carboxyl group. It can be produced by a reaction step (step (II)).

[0060] (Process I) A polycarbonate resin having a carbon-carbon double bond at the polymer chain end is produced by using at least one phenol compound having a carbon-carbon double bond by a reaction means known per se for producing a normal polycarbonate resin. Examples of the reaction method include an interfacial polycondensation method, a melt transesterification method, and a solid-phase transesterification method of a carbonate prepolymer. Among them, from the viewpoint of quantitatively introducing the structure represented by formula (4) into the polymer chain end, a method in which a phenol compound having a carbon-carbon double bond acts as a terminal terminator in the interfacial polycondensation method is preferred.

[0061] Examples of phenol compounds having a carbon-carbon double bond used as end terminators include parahydroxyallylphenol, metahydroxyallylphenol, orthohydroxyallylphenol, etc. From the viewpoint of efficiency of introduction into the polymerization end, orthohydroxyallylphenol is particularly preferred. These may be used alone or in combination of two or more.

[0062] Phenol compounds having no carbon-carbon double bonds may be used in combination as a terminal terminator. Examples of phenol compounds having no carbon-carbon double bonds include phenol, m-methylphenol, p-methylphenol, m-propylphenol, p-propylphenol, 1-phenylphenol, 2-phenylphenol, p-tert-butylphenol, p-cumylphenol, isooctylphenol, and p-long chain alkylphenol. By using these phenol compounds having no carbon-carbon double bonds in combination as a terminal terminator, the amount of carboxyl groups at the polymer chain end can be quantitatively adjusted, and the thermal stability of the organic-inorganic composite composition, the dispersibility of inorganic fine particles, and the flowability during melting can be controlled.

[0063] (Process II) The polycarbonate resin having the carbon-carbon double bond produced in step (I) is reacted with a thiol compound having a carboxyl group (enethiol reaction) to produce a polycarbonate resin having a structure represented by the formula (4). The enethiol reaction is a reaction in which a carbon-carbon double bond and a thiol group are added in a one-to-one ratio. That is, when a thiol is irradiated with light or a radical generator is added, a thiyl radical is easily generated and added to the carbon-carbon double bond. The carbon radical thus generated extracts hydrogen from the thiol group to produce a one-to-one adduct. The thiol group from which hydrogen has been extracted becomes a thiyl radical, so the reaction proceeds in a chain reaction. In this way, the enethiol reaction can be used to quantitatively produce a polycarbonate resin having a carboxyl group in high yield.

[0064] Examples of thiol compounds having a carboxyl group include 3-mercaptopropanoic acid, 3-mercapto-2-methylpropanoic acid, mercaptosuccinic acid, 2-mercaptobenzoic acid, and 1-(mercaptomethyl)cyclopropaneacetic acid.

[0065] In the enethiol reaction, it is preferable to use a radical generator as a reaction catalyst. However, it may be a radical reaction caused by irradiation with light (ultraviolet rays). Examples of radical generators include azo compounds, organic peroxides, etc., and either one that generates radicals by heat or one that generates radicals by irradiation with light can be suitably used. Examples of azo compounds include azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexanecarbonitrile) (ABCN), etc. Examples of organic peroxides include di-tert-butyl peroxide, benzoyl peroxide, etc.

[0066] More specifically, the enethiol reaction can be carried out by dissolving a polycarbonate resin having a carbon-carbon double bond, a thiol compound having a carboxyl group, and a radical generator in an organic solvent and maintaining the mixture under conditions in which radicals are generated. Examples of the organic solvent include alcohols (alkyl alcohols such as ethanol, propanol, and isopropanol, glycols such as ethylene glycol and propylene glycol, etc.), hydrocarbons (aliphatic hydrocarbons such as hexane, alicyclic hydrocarbons such as cyclohexane, aromatic hydrocarbons such as toluene and xylene, etc.), halogenated hydrocarbons (methylene chloride, chloroform, etc.), ethers (chain ethers such as dimethyl ether and diethyl ether, cyclic ethers such as dioxane and tetrahydrofuran, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, ethyl lactate, ethyl butyrate, etc.), ketones (acetone, ethyl methyl ketone, methyl isobutyl ketone, cyclohexanone, N-methyl-2-pyrrolidone, etc.), Examples of organic solvents include cellosolves (methyl cellosolve, ethyl cellosolve, butyl cellosolve, etc.), carbitols (methyl carbitol, ethyl carbitol, butyl carbitol, etc.), propylene glycol monoalkyl ethers (propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol mono n-butyl ether, etc.), glycol ether esters (ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, etc.), amides (N,N-dimethylformamide, N,N-dimethylacetamide, etc.), sulfoxides (dimethyl sulfoxide, etc.), nitriles (acetonitrile, benzonitrile, etc.), and N-methylpyrrolidone. The organic solvent may be used alone or in combination of two or more kinds. The reaction temperature is not particularly limited, but is preferably 50 to 120°C.

[0067] (Other units) As the unit other than the polymer chain end, i.e., the unit of the main chain, various diol compounds can be mentioned. Such diol compounds may be any of aromatic diol compounds, aliphatic diol compounds, and alicyclic diol compounds, and include the diol compounds described in WO 2004 / 111106 and WO 2011 / 021720, and oxyalkylene glycols such as diethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol. These may be used alone or in combination of two or more. Representative specific examples of the diol component are shown below, but the other components of the present invention are not limited thereto.

[0068] Specific examples of aromatic diol compounds include 4,4'-biphenol, 3,3',5,5'-tetrafluoro-4,4'-biphenol, α,α'-bis(4-hydroxyphenyl)-o-diisopropylbenzene, α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (usually referred to as "BPM"), α,α'-bis(4-hydroxyphenyl)-p-diisopropylbenzene, α,α'-bis(4-hydroxyphenyl)-m-bis(1,1,1,3,3,3-hexafluoroisopropyl)benzene, 1,1 ... 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)cyclopentane, 1,1-bis(3-fluoro-4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)perfluorocyclohexane, 4,4'-dihydroxydiphenyl ether, 4,4'- Dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfoxide, 4,4'-dihydroxydiphenyl sulfide (hereinafter sometimes abbreviated as "TDP"), 3,3'-dimethyl-4,4'-dihydroxydiphenyl sulfide (hereinafter sometimes abbreviated as "HMPS"), 3,3'-dimethyl-4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxy-3,3'-diphenyl sulfide, 4,4'-dihydro 4,4'-dihydroxy-3,3'-diphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyl sulfone, 1,1-bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly referred to as "BPA"), 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxy-3-methylphenyl)propane (commonly referred to as "BPC"), 9,9-bis(4-hydroxyphenyl)fluorene (hereinafter sometimes abbreviated as "BPF"), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF"), 9,9-bis(4-hydroxy-3-phenylphenyl)fluorene (hereinafter sometimes abbreviated as "BPPF"), 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 2,2-bis(4-hydroxy-3-phenylphenyl)propane, 2,2-bis(3-isopropyl-4-hydroxyphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(3-tert-butyl-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)butane, 4,4-bis(4-hydroxyphenyl)heptane, 2,2-bis(4-hydroxyphenyl)octane, 1,1-bis(4-hydroxyphenyl)decane, 1,1-bis(3-methyl-4-hydroxyphenyl)decane, 1,1-bis(2,3-dimethyl-4-hydroxyphenyl)decane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, 2,2-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, Bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (commonly referred to as "BPAF"), 6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 7,7'-dimethyl-6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 7,7'-diphenyl-6,6'-dihydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, 2,2-bis(4-hydroxy-3-methylphenyl)-1,1,1,3,3,3-hexafluoropropane, Fluoropropane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3-fluoro-4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane, and 2,2-bis(3,5-difluoro-4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(3,5-dibromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, and 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane.

[0069] Among the above, BPM, TDP, HMPS, BPA, BPC, BPF, BCF, and BPPF are preferred.

[0070] Aliphatic diol compounds include 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-n-butyl-2-ethyl-1, Examples of the alkyl ether ester include 3-propanediol, 2,2-diethyl-1,3-propanediol, 2,4-diethyl-1,5-pentanediol, 1,2-hexane glycol, 1,2-octyl glycol, 2-ethyl-1,3-hexanediol, 2,3-diisobutyl-1,3-propanediol, 2,2-diisoamyl-1,3-propanediol, and 2-methyl-2-propyl-1,3-propanediol.

[0071] Examples of the alicyclic diol compound include cyclohexanedimethanol, tricyclodecane dimethanol, adamantanediol, pentacyclopentadecanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and isosorbide (1,4;3,6-dianhydro-D-sorbitol).

[0072] (Production method of polycarbonate resin polymer) In a reaction using, for example, phosgene as a carbonate precursor, the reaction is usually carried out in the presence of an acid binder and a solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an amine compound such as pyridine, is used. As the solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is several minutes to 5 hours.

[0073] The transesterification reaction using, for example, a carbonic acid diester as a carbonate precursor is carried out by a method in which a predetermined ratio of aromatic dihydroxy components is heated and stirred with a carbonic acid diester under an inert gas atmosphere, and the alcohol or phenols produced are distilled off. The reaction temperature varies depending on the boiling point of the alcohol or phenols produced, but is usually in the range of 120 to 300°C. The reaction is completed by reducing the pressure from the beginning of the reaction and distilling off the alcohol or phenols produced. In order to promote the reaction, a catalyst usually used in transesterification reactions can also be used. Examples of the carbonic acid diester used in the transesterification reaction include diphenyl carbonate, dinaphthyl carbonate, bis(diphenyl)carbonate, dimethyl carbonate, diethyl carbonate, and dibutyl carbonate. Among these, diphenyl carbonate is particularly preferred.

[0074] The polycarbonate resin of the present invention can be copolymerized with a fatty acid as required, for example, 1,10-dodecanedioic acid, adipic acid, hexanedioic acid, isophthalic acid, 1,3-benzenedicarboxylic acid, terephthalic acid, 1,4-benzenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 3-hydroxybenzoic acid, and 4-hydroxybenzoic acid.

[0075] The polycarbonate resin of the present invention includes polyester carbonate copolymerized with aromatic or aliphatic (including alicyclic) difunctional carboxylic acids. The aliphatic difunctional carboxylic acids are preferably α,ω-dicarboxylic acids. Examples of the aliphatic difunctional carboxylic acids include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. These carboxylic acids may be copolymerized to the extent that the purpose is not hindered. The polycarbonate resin of the present invention may also be copolymerized with a structural unit containing a polyorganosiloxane unit, if necessary.

[0076] The polycarbonate resin of the present invention can be copolymerized with a structural unit containing a trifunctional or higher polyfunctional aromatic compound to form a branched polycarbonate, if necessary. Examples of trifunctional or higher polyfunctional aromatic compounds used in the branched polycarbonate include 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, and trisphenols such as 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol. Among them, 1,1,1-trisphenols such as 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2, 2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, and 4-{4-[1,1-bis(4-hydroxyphenyl)ethyl]benzene}-α,α-dimethylbenzylphenol are preferred. The structural units derived from such polyfunctional aromatic compounds preferably account for 0.03 to 1.5 mol %, more preferably 0.1 to 1.2 mol %, and particularly preferably 0.2 to 1.0 mol %, of the total of 100 mol %, including the structural units derived from other divalent components.

[0077] The branched structural unit may be derived not only from a polyfunctional aromatic compound, but also from a side reaction occurring during a polymerization reaction by a melt transesterification method without using a polyfunctional aromatic compound. 1 It can be calculated by H-NMR measurement.

[0078] (viscosity average molecular weight) The viscosity average molecular weight of the polycarbonate resin of the present invention is preferably 5,000 to 40,000, more preferably 8,000 to 30,000, further preferably 10,000 to 25,000, and particularly preferably 12,000 to 23,000. When it is in such a range, it is preferable because it has an excellent balance between moldability and mechanical strength.

[0079] The viscosity average molecular weight of the polycarbonate resin of the present invention is calculated by first calculating the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7

[0080] (Glass transition temperature: Tg) The glass transition temperature (Tg) of the polycarbonate resin is preferably 90 to 200°C, more preferably 100 to 190°C, and further preferably 110 to 180°C. If the Tg is within the above range, the heat resistance stability and moldability are good when used as an optical molded body, which is preferable. The glass transition temperature (Tg) is measured using a 2910 type DSC manufactured by TA Instruments Japan Co., Ltd. at a heating rate of 20°C / min.

[0081] (Amount of carboxyl groups) The amount of carboxyl groups in the polycarbonate resin of the present invention is preferably 1 to 200 eq / ton, more preferably 10 to 170 eq / ton, further preferably 30 to 150 eq / ton, and particularly preferably 50 to 120 eq / ton. If the amount of carboxyl groups is equal to or more than the lower limit, the dispersion stability of inorganic fine particles under high temperature conditions is sufficient, and a transparent organic-inorganic hybrid composition can be obtained. If the amount is equal to or less than the upper limit, the molecular weight reduction of the polycarbonate resin can be suppressed, which has a favorable effect on the physical properties.

[0082] The amount of carboxyl groups in the present invention can be measured, for example, as follows: First, a polycarbonate resin is dissolved in benzyl alcohol under a nitrogen atmosphere, and titrated with a benzyl alcohol solution of sodium hydroxide using phenol red as an indicator, and the amount of carboxyl groups is calculated from the amount of the solution dropped.

[0083] <Inorganic fine particles> The inorganic fine particles used in the present invention are preferably modified with a surface modifier. The inorganic fine particles preferably have an average particle size in the nanoscale range of 20 nm or less. Those modified with a surface modifying agent having an acidic functional group are preferably used.

[0084] Examples of inorganic fine particles include ZrO2 (zirconium oxide), TiO2 (titanium oxide), SnO2 (tin oxide), SiO2 (silicon oxide), Al2O3 (aluminum oxide), etc. Among them, in the present invention, ZrO2 and TiO2 are preferred from the viewpoint of use as optical members and optical components, and ZrO2 is particularly preferred.

[0085] The surface modifier for inorganic fine particles in the present invention is not particularly limited as long as it can ensure the dispersibility of inorganic fine particles in polycarbonate resins to be composited, but it is preferable to have an acidic functional group such as a sulfonic acid group, a phosphonic acid group, a phosphinic acid group, or a carboxylic acid group, since it is excellent in dispersibility and refractive index improvement effect. Representative specific examples of the surface modifier are shown below, but the surface modifier of the present invention is not limited thereto. They may be used alone, or a mixture of two or more types may be used. In particular, when dispersing inorganic fine particles after surface modification treatment in a resin, it is desirable to appropriately select and use a surface modifier that is likely to improve affinity with the resin depending on the type of the resin.

[0086] Examples of sulfonic acids include alkylsulfonic acids such as butanesulfonic acid, hexanesulfonic acid, and dodecanesulfonic acid, and arylsulfonic acids such as benzenesulfonic acid, methylbenzenesulfonic acid, and dodecylbenzenesulfonic acid. Among these, arylsulfonic acids are preferred in view of dispersibility in resins and the effect of improving the refractive index.

[0087] Examples of the phosphonic acid include alkyl phosphonic acids such as propane phosphonic acid, and aryl phosphonic acids such as benzene phosphonic acid. Among these, aryl phosphonic acids are preferred in view of dispersibility in resins and the effect of improving the refractive index.

[0088] Examples of phosphinic acid include alkyl phosphinic acids such as dimethylphosphinic acid, diethylphosphinic acid, and di(2-ethylhexyl)phosphinic acid, and aryl phosphinic acids such as phenylphosphinic acid and diphenylphosphinic acid. In addition, by using thiophosphinic acid or dithiophosphinic acid in which the oxygen atom constituting the phosphinic acid group is replaced with a sulfur atom, inorganic fine particles having a higher refractive index than when using phosphinic acid can be obtained. Among them, in view of dispersibility in resin and the effect of improving the refractive index, aryl phosphinic acid is preferred, phenylphosphinic acid and diphenylphosphinic acid are more preferred, and diphenylphosphinic acid is particularly preferred.

[0089] Examples of the carboxylic acid include alkyl carboxylic acids such as butanoic acid, isobutanoic acid, methacrylic acid, hexanoic acid, octanoic acid, oleic acid, linoleic acid, and lauric acid, and aryl carboxylic acids such as benzoic acid, hydroxybenzoic acid, and phenoxybenzoic acid. In addition, by using thiocarboxylic acid or dithiocarboxylic acid in which the oxygen atom constituting the carboxyl group of the carboxylic acid is replaced with a sulfur atom, inorganic fine particles having a higher refractive index than when using carboxylic acid can be obtained. Among them, in consideration of dispersibility in resin and the effect of improving the refractive index, aryl carboxylic acid is preferred, phenoxybenzoic acid having a phenoxy group at the ortho, meta, or para position is more preferred, and paraphenoxybenzoic acid is particularly preferred.

[0090] The surface modification of inorganic fine particles in the present invention is carried out, for example, by the following steps. That is, a surface modifier having an acidic functional group is added to a mixture of a transparent aqueous dispersion in which hydrophilic inorganic fine particles having an average particle size of about 20 nm or less are dispersed, and methanol, and then the water and methanol are removed by azeotropy and the solvent is replaced with toluene or methylene chloride to prepare a toluene dispersion or methylene chloride dispersion in which the surface-modified inorganic fine particles are dispersed. The solvent is then distilled off to obtain a white powder of the surface-modified inorganic fine particles.

[0091] In the inorganic fine particles modified with a surface modifier, the content of the surface modifier is preferably 1 to 30 mass % relative to the inorganic fine particles, more preferably 3 to 28 mass %, and particularly preferably 5 to 25 mass %, in consideration of dispersibility in resin and the effect of improving the refractive index. From the viewpoint of dispersibility in the resin composite, the higher the content of the surface modifier, the better, and from the viewpoint of the effect of improving the refractive index, the lower the content of the surface modifier, the better. It is desirable to appropriately adjust the content of the surface modifier according to the dispersibility and the desired refractive index.

[0092] <Components other than polycarbonate resin and inorganic fine particles> The organic-inorganic hybrid composition of the present invention may contain, in addition to the polycarbonate resin and inorganic fine particles, functional agents known per se, such as a release agent, a heat stabilizer, an ultraviolet absorber, a flow modifier, and an antistatic agent, within the scope of not impairing the effects of the present invention.

[0093] The method of blending the resin other than the polycarbonate resin and the additives into the organic-inorganic composite composition of the present invention is not particularly limited, and any known method can be used. The most commonly used method is to premix the polycarbonate resin, inorganic fine particles, and additives, then put them into an extruder to melt-knead, cool the extruded thread, and cut it with a pelletizer to produce a pellet-shaped molding material.

[0094] <Method of producing organic-inorganic composite composition> The method for producing the organic-inorganic hybrid composition of the present invention includes obtaining a polycarbonate resin having a structure represented by the above formula (1) at a polymer chain end, and dispersing inorganic fine particles that have been surface-modified with a surface modifier in the polycarbonate resin.

[0095] The process for dispersing inorganic fine particles in a polycarbonate resin is not particularly limited, but specific examples thereof include a method of mixing a polycarbonate resin solution with an inorganic fine particle dispersion, and a method of melt-mixing a polycarbonate resin powder with an inorganic fine particle powder, and any of these methods may be used to prepare the dispersion.

[0096] For example, in the method of mixing a polycarbonate resin solution and an inorganic fine particle dispersion, the polycarbonate resin solution and the inorganic fine particle dispersion may be mixed at once, or the polycarbonate resin solution may be gradually dropped into the inorganic fine particle dispersion and mixed. A plasticizer may be present, and such a plasticizer may be added to the resin solution or the inorganic fine particle dispersion in advance, or may be added when the resin solution and the inorganic fine particle dispersion are mixed.

[0097] The content of the inorganic fine particles in the organic-inorganic hybrid composition of the present invention is preferably 1 to 50 mass%, more preferably 3 to 40 mass%, and most preferably 5 to 30 mass%. If the surface-modified inorganic fine particles are less than the lower limit, it is difficult to obtain the effect of containing the inorganic fine particles, and if the content exceeds the upper limit, the strength of the organic-inorganic hybrid composition decreases.

[0098] An organic-inorganic composite composition containing a polycarbonate resin having the structure represented by formula (1) at the polymer chain end and inorganic fine particles surface-modified with a surface modifier can be added to another resin as a master resin and used in a mixed state. By using this method, it is possible to adjust the refractive index and Abbe number within any range and obtain an organic-inorganic composite composition suitable as an optical resin.

[0099] (Molding method) The organic-inorganic composite composition of the present invention can be molded by a general molding method for polycarbonate resin, such as injection molding, extrusion molding, compression molding, solution casting, etc. The organic-inorganic composite composition of the present invention has excellent transparency and a high refractive index, and can be used as various molded articles, particularly optical lenses, optical disks, liquid crystal panels, optical cards, sheets, etc. The composition can be advantageously used as a molded article suitable for structural materials for optical components such as films, optical fibers, connectors, vapor-deposited plastic reflectors, and displays; electric and electronic components such as exteriors and front panels of personal computers and mobile phones; automotive applications such as automobile headlamps and windows; or functional material applications, and is particularly suitable for optical lenses and optical films.

[0100] (Average particle size) In the organic-inorganic hybrid composition of the present invention, the inorganic fine particles have an average particle size of preferably 1 to 100 nm, more preferably 1 to 50 nm, and further preferably 1 to 20 nm. If the average particle size exceeds the upper limit of this range, the transparency of the organic-inorganic hybrid composition may be insufficient.

[0101] (transmittance) The organic-inorganic hybrid composition of the present invention preferably has high transmittance. The D-line transmittance of a molded article having a thickness of 1 mm is preferably 70% or more, and more preferably 80% or more. By satisfying such characteristics, the composition can be suitably used for optical lenses and optical films.

[0102] (Refractive Index) The refractive index (hereinafter sometimes abbreviated as nD) of the organic / inorganic hybrid composition of the present invention at a wavelength of 589 nm measured at 25° C. is preferably 1.500 to 2.000. When the refractive index is equal to or higher than the lower limit, the spherical aberration of the lens can be reduced, and further the focal length of the lens can be shortened. EXAMPLES

[0103] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the examples, "parts" means "parts by mass." The polycarbonate resin, inorganic fine particles, and evaluation methods used in the examples are as follows.

[0104] <Evaluation method> (composition ratio) Each repeating unit was measured by proton NMR using a JNM-AL400 manufactured by JEOL Ltd., and the polymer composition ratio (molar ratio) was calculated.

[0105] (viscosity average molecular weight) The specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of sample dissolved in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and the viscosity average molecular weight Mv was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mv 0.83 c=0.7

[0106] (Glass transition temperature (Tg)) Using 8 mg of sample, measurements were performed using a thermal analysis system DSC-2910 manufactured by TA Instruments Co., Ltd. under conditions of nitrogen atmosphere (nitrogen flow rate: 40 ml / min) and heating rate: 20°C / min in accordance with JIS K7121.

[0107] (Amount of carboxyl groups) The sample was dissolved in benzyl alcohol under a nitrogen atmosphere, and the benzyl alcohol of sodium hydroxide was The calculation was made by titrating alcohol solution using phenol red as an indicator.

[0108] (Moldability) The pellets melted and mixed in the extruder were molded in an injection molding machine (J-75E3 manufactured by Japan Steel Works) under conditions of a cylinder temperature of 300°C, a mold temperature of 80°C, a pressure holding time of 20 seconds, and a cooling time of 20 seconds to form a three-layered resin plate with a width of 50 mm, a length of 90 mm, and thicknesses of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side, and various evaluations were carried out. When a three-layered resin plate was obtained under the above conditions, the moldability was evaluated as "◎", when a resin plate was obtained but had poor appearance such as the generation of air bubbles, it was evaluated as "〇", and when a resin plate could not be obtained due to insufficient resin strength due to hydrolysis, etc., the moldability was evaluated as "×".

[0109] (Average particle size) The pellets melted and mixed in the extruder were press molded in a hot press molding machine (Shinto Metal Industries Co., Ltd., compression molding machine: SFV-10, vacuum pump unit: GXD-360) to obtain a molded plate with a thickness of approximately 1 mm. The press molding conditions were a mold temperature of 220°C, a primary pressure of 1 MPa (30 seconds), and a secondary pressure of 1.5 MPa (5 minutes). This molded plate was cut to prepare ultrathin slices, which were attached to a grid (JEOL Ltd., EM FINE GRID No. 2632 F-200-CU 100PC / CA), and observed using a JEOL Ltd., transmission electron microscope, TEM JEM-2100, at an accelerating voltage of 200 kV. Using a micrograph taken at a magnification of 100,000 times, particle analysis was performed using the image analysis software WinROOF Ver.6.6 (Mitani Shoji Co., Ltd.) to obtain the average size and particle size distribution (frequency distribution) of inorganic fine particles in the sample slice. Here, the maximum major axis (the length when two arbitrary points on the outer contour of the particle are selected so that the length between them is the maximum) was used as the size of each particle. Similar analysis was performed on three sample slices, and the average value was used as the value for each sample.

[0110] (transparency) The three-layer resin plate obtained by injection molding was evaluated as having a spectral transmittance of 80% or more at 589 nm in a thickness of 1.0 mm, and as "good" if it was less than 80%.

[0111] (Refractive Index) The refractive index (nD) (wavelength: 589 nm) of the three-stage resin plate obtained by injection molding at 25° C. was measured using an ATAGO DR-M2 Abbe refractometer.

[0112] <Production of polycarbonate resin> (Production Example 1) (Polymerization reaction) A reactor equipped with a thermometer, a stirrer, and a reflux condenser was charged with 8,523 parts of ion-exchanged water and 3787 parts of 25% aqueous sodium hydroxide solution, and 901 parts of 2,2-bis(4-hydroxyphenyl)propane (hereinafter sometimes referred to as BPA) and 1,010 parts of 2,2-bis(4-hydroxy-3-methylphenyl)propane (hereinafter sometimes referred to as BPC) as dihydric phenols, and 5.73 parts of hydrosulfite were dissolved therein. Then, 6708 parts of methylene chloride was added, and 1,000 parts of phosgene (hereinafter sometimes abbreviated as "FH") was blown in over 70 minutes at 16 to 24°C under stirring. 631 parts of an aqueous 25% sodium hydroxide solution was added, and a solution of 58.2 parts of tertiary butyl 4-hydroxybenzoate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 580 parts of methylene chloride was added as a terminal terminator, and the mixture was stirred to an emulsified state, and then stirred vigorously again. While stirring, 2.0 parts of triethylamine was added when the reaction solution was at 28°C, and the reaction was terminated by continuing stirring at a temperature of 26 to 31°C for 1 hour. After the reaction was completed, the organic phase was separated, diluted with methylene chloride and repeatedly washed with water, and when the washing solution became neutral, it was washed with hydrochloric acid acid water. Thereafter, it was repeatedly washed with ion-exchanged water, and the conductivity of the aqueous phase was When the viscosity of the resin was almost the same as that of ion-exchanged water, it was put into a kneader filled with warm water and the methylene chloride was evaporated while stirring to obtain a resin powder. After dehydration, it was dried at 100°C for 12 hours in a hot air circulation dryer.

[0113] (Acid denaturation reaction) 500 parts of the resin powder was placed in a reactor equipped with a thermometer, a stirrer, and a reflux condenser, dissolved in 650 parts of methylene chloride, and 500 parts of trifluoroacetic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added over 30 minutes while stirring, and the reaction was terminated by continuing stirring at a temperature of 20 to 30°C for 5 hours. After the reaction was completed, the mixture was diluted with methylene chloride and repeatedly washed with ion-exchanged water until the conductivity of the aqueous phase became almost the same as that of the ion-exchanged water. The mixture was then placed in a kneader filled with warm water, and the methylene chloride was evaporated while stirring to obtain a resin powder. After dehydration, the mixture was dried at 100°C for 12 hours using a hot air circulation dryer. The viscosity average molecular weight of the obtained resin was 19,800, the glass transition temperature was 130°C, and the amount of carboxyl groups was 68eq / ton.

[0114] (Production Example 2) This was produced in the same manner as in Production Example 1, except that the dihydric phenol was changed to 1,988 parts of BPA, and the end terminators were changed to 54.1 parts of tert-butyl 4-hydroxybenzoate and 7,401 parts of methylene chloride. (Acid denaturation reaction) It was produced in the same manner as in Production Example 1. The viscosity average molecular weight of the obtained resin was 22,300, the glass transition temperature was 148° C., and the amount of carboxyl groups was 72 eq / ton.

[0115] (Production Example 3) (Polymerization reaction) This was produced in the same manner as in Production Example 1, except that the dihydric phenol was changed to 2,538 parts of 9,9-bis(4-hydroxy-3-phenylphenyl)fluorene (hereinafter sometimes referred to as BPPF) and 735 parts of 4,4'-dihydroxydiphenyl sulfide (hereinafter sometimes referred to as TDP), and the end terminators were changed to 83.3 parts of tert-butyl 4-hydroxybenzoate and 7,154 parts of methylene chloride. (Acid denaturation reaction) It was produced in the same manner as in Production Example 1. The viscosity average molecular weight of the resulting resin was 15,000, the glass transition temperature was 179° C., and the amount of carboxyl groups was 112 eq / ton.

[0116] (Production Example 4) (Polymerization reaction) A resin powder was obtained in the same manner as in Production Example 1, except that the dihydric phenol was changed to 901 parts of BPA and 1010 parts of BPC, and the end terminator was changed to 40.2 parts of 2-allylphenol (manufactured by Tokyo Chemical Industry Co., Ltd.). (Acid denaturation reaction) In a reactor equipped with a thermometer, a stirrer, and a reflux condenser, 500 parts of the resin powder and 5,000 parts of 1,2-dichloroethane were added and dissolved, and then 117 parts of azobisisobutyronitrile (hereinafter AIBN) and 150 parts of 3-mercaptopropanoic acid were added, and the mixture was heated to 70°C under a nitrogen atmosphere and reacted for 4 hours. After the reaction was completed, the reaction solution was added to acetone to precipitate the polycarbonate resin, and the precipitate was collected by vacuum filtration. Next, the precipitate was dissolved in methylene chloride and added to acetone to precipitate the polycarbonate resin, and the precipitate was collected by vacuum filtration. The obtained precipitate was collected by vacuum filtration and dried to obtain a polycarbonate resin powder. The viscosity average molecular weight of the obtained resin was 20,300, the glass transition temperature was 136°C, and the amount of carboxyl groups was 58eq / ton.

[0117] (Production Example 5) (Polymerization reaction) A resin powder was obtained in the same manner as in Production Example 1, except that the dihydric phenol was changed to 1,712 parts of BPA and 122 parts of 2,2-bis(3-allyl-4-hydroxyphenyl)propane (hereinafter referred to as BPDAL), and the end terminator was changed to 47.3 parts of p-tert-butylphenol. (Acid denaturation reaction) It was produced in the same manner as in Production Example 4. The viscosity average molecular weight of the obtained resin was 20,400, the glass transition temperature was 132° C., and the amount of carboxyl groups was 228 eq / ton.

[0118] (Production Example 6) The resin was produced in the same manner as in Production Example 1 (polymerization reaction), except that the end terminator was changed to 45.0 parts of p-tert-butylphenol, and no acid modification reaction was carried out. The viscosity average molecular weight of the resulting resin was 20,000, and the glass transition temperature was 131°C.

[0119] (Production Example 7) The resin was produced in the same manner as in Production Example 2 (polymerization reaction), except that the end terminator was changed to 41.8 parts of p-tert-butylphenol, and no acid modification reaction was carried out. The viscosity average molecular weight of the resulting resin was 22,000, and the glass transition temperature was 146°C.

[0120] (Production Example 8) The resin was produced in the same manner as in Production Example 3 (polymerization reaction), except that the end terminator was changed to 64.4 parts of p-tert-butylphenol, and no acid modification reaction was carried out. The viscosity average molecular weight of the resulting resin was 15,200, and the glass transition temperature was 180°C.

[0121] <Production of inorganic fine particles> (Production Example 9) In a 2L eggplant flask equipped with a stirrer tip, 3.84 g of paraphenoxybenzoic acid was added as a surface modifier, and 300 mL of methanol and 700 mL of chloroform were added to dissolve the mixture. Next, 37.2 g of ZrO2 aqueous dispersion (SZR-W manufactured by Sakai Chemical Industry Co., Ltd.) was added dropwise over 15 minutes. The mixture was stirred at room temperature for 1 hour, and the solvent was distilled off until the volume was about 200 mL using a rotary evaporator. The distillation was performed by reducing the pressure to a level that did not cause bumping in the liquid phase. 300 mL of methanol and 700 mL of chloroform were added to the mixture to make a transparent dispersion with no interface again, and the solvent was distilled off again until the volume was about 200 mL. This operation was repeated three times to obtain a powdery solid.

[0122] 500mL of methylene chloride was added to the solid, again forming a transparent dispersion with no interface, and the solvent was distilled off until the volume was about 100mL. This operation was repeated three times, replacing the water / methanol / chloroform mixed solvent with methylene chloride alone to obtain a methylene chloride dispersion of ZrO2 fine particles. Furthermore, this methylene chloride dispersion was vacuum dried at room temperature for 24 hours to remove the methylene chloride, and then further dried at 120°C for 48 hours to obtain a powder of surface-modified ZrO2.

[0123] (Production Example 10) A surface-modified ZrO2 powder was obtained in the same manner as in Production Example 9, except that 1.34 g of diphenylphosphinic acid was used as the surface modifier.

[0124] <Production of Organic-Inorganic Composite Composition> [Examples 1 to 6, Comparative Examples 1 to 4] The inorganic fine particles were dispersed in methylene chloride, and the methylene chloride solution of the polycarbonate resin was added dropwise over 5 minutes, followed by stirring for 30 minutes. The mixture was dried for 10 minutes to remove methylene chloride, and further dried at 120°C for 24 hours to obtain flakes of organic-inorganic composite. The flakes were melted and kneaded in a twin-screw extruder (KZW15-25MG, manufactured by Technobel Co., Ltd.) at a cylinder and die temperature of 300°C, and the extruded resin was cut with a pelletizer while being cooled in a water tank to obtain pellets. The extruded pellets were molded into a three-stage resin plate with a width of 50 mm, a length of 90 mm, and a thickness of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side at a cylinder temperature of 300°C, a mold temperature of 80°C, a pressure retention time of 20 seconds, and a cooling time of 20 seconds using an injection molding machine (J-75E3, manufactured by Japan Steel Works, Ltd.). Various evaluations were performed, and the results are shown in Table 3. The type of resin used, the type of surface modifier, and the amount of inorganic fine particles added are as shown in Table 3.

[0125] [Table 1]

[0126] [Table 2]

[0127] [Table 3]

[0128] When the polycarbonate resin of the present invention was used as in Examples 1 to 6, an organic-inorganic composite composition excellent in moldability, transparency, and refractive index was provided. When a polycarbonate resin having a carboxyl group in the side chain but not at the polymer chain end was used as in Comparative Example 1, decomposition was significant and melt moldability was poor. When a polycarbonate resin having no carboxyl group at the polymer chain end was used as in Comparative Examples 2 to 4, inorganic fine particles could not be uniformly dispersed, the fine particles aggregated, and the transmittance was low.

[0129] Figure 1 shows a TEM image of the organic-inorganic composite composition obtained in Example 1. The composition was highly transparent and the inorganic fine particles were uniformly dispersed.

[0130] FIG. 2 shows a TEM image of the organic-inorganic composite composition obtained in Comparative Example 3. The particles were agglomerated. [Industrial Applicability]

[0131] The organic-inorganic hybrid composition of the present invention is excellent in transparency, refractive index, and moldability. In addition, the properties such as refractive index can be adjusted as desired by adjusting the content of inorganic fine particles. Therefore, the molded products, films, and sheets obtained by using the present invention can be used in various fields.

Claims

1. An organic-inorganic hybrid composition comprising a polycarbonate resin having a structural unit represented by the following formula (1) at a polymer chain end, and inorganic fine particles: 【Chemistry 1】 (In formula (1), R 1 and R 2 may be independent or the same, and represent at least one group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group, an alkoxy group, a cycloalkyl group, a cycloalkoxy group, an alkenyl group, an aryl group, an aryloxy group, an aralkyl group, an aralkyloxy group, a nitro group, an aldehyde group, and a cyano group, a and b each represent an integer of 1 to 2, and X represents a group represented by the following formula (2): 【Chemistry 2】 where R is a divalent group represented by 3 and R 4 each independently represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group; R 4 The hydrogen atoms in may be substituted with carboxyl groups.

2. 2. The organic-inorganic hybrid composition according to claim 1, wherein the molar ratio of the polymer chain ends is from 1.0 mol % to 10 mol % based on 100 mol % of all carbonate repeating units.

3. The organic-inorganic hybrid composition according to claim 1 or 2, wherein the formula (1) includes a structural unit represented by the following formula (4): 【Chemistry 3】 (In formula (4), R 7 represents at least one group selected from the group consisting of an alkylene group, an aralkylene group, an arylene group, and a cycloalkylene group.

4. 4. The organic-inorganic hybrid composition according to claim 1, wherein the polycarbonate resin has a carboxyl group content of 1 eq / ton to 200 eq / ton.

5. 5. The organic-inorganic hybrid composition according to claim 1, wherein the surfaces of the inorganic fine particles are modified with a surface modifying agent.

6. The organic-inorganic hybrid composition according to claim 5 , wherein the surface modifier has an acidic functional group.

7. 7. The organic-inorganic hybrid composition according to claim 6, wherein the acidic functional group is at least one acidic functional group selected from the group consisting of a sulfonic acid group, a phosphonic acid group, a phosphinic acid group, and a carboxylic acid group.

8. 8. The organic-inorganic hybrid composition according to claim 5, wherein the surfaces of the inorganic fine particles are modified with the surface modifying agent in an amount of 1 to 30% by mass based on the inorganic fine particles.

9. The organic-inorganic hybrid composition according to any one of claims 1 to 8, wherein the inorganic fine particles have an average particle size of 1 to 20 nm.

10. The organic-inorganic hybrid composition according to any one of claims 1 to 9, wherein the content of the inorganic fine particles is 1 to 50% by mass based on the polycarbonate resin.

11. The inorganic fine particles are ZrO 2 (Zirconium oxide), TiO 2 (Titanium oxide), SnO 2 (Tin oxide), SiO 2 (silicon oxide), and Al 2 O 3 The organic-inorganic hybrid composition according to any one of claims 1 to 10, wherein the organic-inorganic hybrid composition is at least one selected from the group consisting of (aluminum oxide).

12. A molded article obtained by using the organic / inorganic hybrid composition according to any one of claims 1 to 11.

13. A film or sheet obtained by using the organic-inorganic hybrid composition according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Production of polycarbonate resin containing terminal carboxyl group

    JP1988003022A

  • Organic-inorganic composite material, optical component and production method thereof

    JP2009029939A

  • Production process of optical resin composition

    JP2011038012A

  • Polycarbonate resin composition and molded article thereof

    JP2017186463A

  • Organic-inorganic composite composition, and molding and optical component containing the same

    JP2018138624A

Cited By

  • Organic-inorganic composite composition

    JP2024123119A